Recent retreat at a temperate Icelandic glacier in the context of the last ~80 years of climate change in the North Atlantic region. - Chandler, B.M.P.; Evans, D.J.A.; Roberts, D.H. (arktos, 2016)
Over recent decades, glaciers outside of Greenland and Antarctica have displayed accelerating rates of mass loss and ice-frontal retreat, and this has been associated with unequivocal climatic and oceanic warming. Icelandic glaciers are particularly sensitive to climate variations on short-term timescales owing to their maritime setting, and have shown rapid rates of retreat and mass loss during the past decade. This study uses annual moraine spacing as a proxy for ice-frontal retreat to examine variability in glacier retreat at Skálafellsjökull, SE Iceland, over the last ~80 years. Two pronounced six-year periods (1936–1941 and 1951–1956) of ice-frontal retreat are recognised in the record for comparison with the most recent phase of retreat (2006–2011), and these three retreat phases are shown to be similar in style and magnitude. Analysis of climate data indicates that these periods of glacier retreat are associated with similar summer air temperature values, which is a key control on Icelandic terminus variations. This demonstrates that both the most recent phase of ice-frontal retreat at Skálafellsjökull and the recent warming of summer temperatures are not unusual in the context of the last ~80 years. These findings demonstrate the importance of placing observations of contemporary glacier change in a broader decadal- to centennial-scale context.